Impact of early tracheostomy on resource utilization and patient outcomes in trauma ICU patients: A retrospective cohort study from southern India - Rajesh Kamath; Sakshi Deshpande; Gwendolen Rodrigues; Tarushree Bari; Vishwajeet Singh; Sandesh Kini; Nahima Akthar; Gavi Salimath (PLoS ONE, 2025)
Introduction A tracheostomy is an important intervention for trauma patients referred to intensive care units (ICUs). Trauma patients often require prolonged intubation; timing of tracheostomy remains debated.The purpose of this study is to determine the impact of early tracheostomy on critical metrics such as mechanical ventilation duration, ICU length of stay (LOS) and ventilator acquired pneumonia (VAP) in trauma patients in ICU settings. Methods We conducted a retrospective cohort study of 383 trauma patients who underwent tracheostomy in a tertiary teaching hospital ICU (January 2018–December 2022). Inclusion: trauma patients with temporary tracheostomy; Exclusion: permanent tracheostomies. Early tracheostomy (ET) was defined as ≤7 days of mechanical ventilation, late (LT) as >7 days. The dataset includes demographic information, Acute physiology and chronic health evaluation II score, Simplified acute physiology score II, Glasgow coma scale score, Injury severity Score, type and cause of injuries, ICU outcomes, length of stay and rates of ventilator-associated pneumonia (VAP). Data were analyzed using Mann–Whitney U and Chi-square tests; significance at p < 0.05.. The study involved a comparison of the duration of mechanical ventilation, ICU LOS, VAP rates and extubation trials between patients who underwent ET and LT. Results Of the 804 patients who underwent tracheostomies from January 2018 to December 2022, 383 were trauma patients and were included in the study. There were no significant differences between the two groups in terms of age, sex, Acute physiology and chronic health evaluation II score, Simplified acute physiology score II and Injury severity score. The incidence of VAP was lower in the ET cohort (15.9%) than in the LT cohort (47.4%). The percentage of extubation trials was found to be higher in the LT cohort (43.1%) than in the ET cohort (9.3%), resulting in prolonged ICU LOS. Patients with an ET had a significantly shorter ICU LOS median of 15 days (IQR 13,17) and a mechanical ventilation median of 13 days (IQR 11,14) than LT patients who had an ICU LOS median of 33 days (IQR 30,36) and a mechanical ventilation median of 31 days (IQR 27,33) respectively. Conclusion Implementing an early tracheostomy protocol for trauma patients in the ICU is associated with a decreased incidence of VAP, shorter duration of mechanical ventilation and shorter ICU LOS while maintaining consistent ICU and hospital outcomes. The adoption of a standardized approach to perform early tracheostomy helps in improving resource utilization and patient outcomes in trauma patients.